Surgical Aspects of Donor Hand Recovery for Transplantation - Banegas, Rodrigo N.; Moreno, Rodrigo; Duggal, Anil; Breidenbach, Warren C., III (Journal of Reconstructive Microsurgery, 2012)
The purpose of this article is to share our institution's experience in optimizing the suitability of composite donor tissue for use in hand transplantation. The centerpiece of this process includes procurement techniques, preservation and timing issues, and anatomical matching. Recovery of the donor hand must proceed in an efficient, organized, and expedient manner. Proper timing of the donor operation not only ensures the quality of donor tissue and outcome for the hand recipient, but also allows surgeons recovering other organs to obtain high quality tissue for those recipients. Timing remains a critical factor in preserving tissue after removal from the donor. We will also consider the factors of temperature and preservation solution during transport.
Keywords: hand transplantation; hand donor operation; hand procurement; hand recovery